2021
DOI: 10.1182/bloodadvances.2020003741
|View full text |Cite|
|
Sign up to set email alerts
|

COVID-19 in individuals with sickle cell disease/trait compared with other Black individuals

Abstract: In the United States, COVID-19 has disproportionately affected Black persons. Sickle cell disease (SCD) and sickle cell trait (SCT) are genetic conditions that occur predominantly among Black individuals. It is unknown if individuals with SCD/SCT are at higher risk of severe COVID-19 illness compared with Black individuals who do not have SCD/SCT. The objective of our study was to compare COVID-19 outcomes, including the disease manifestations, hospitalization, and death, among individuals with SCD/SCT vs Blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
74
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 26 publications
10
74
1
3
Order By: Relevance
“…However, SCD patients could have other severe outcomes not evaluated here (e.g., pain or pneumonia). 12 The mortality rate in our SCD patients (6%-8%) is comparable to those reported in the US 6 and UK registries 13 (7.3% and 8.4%, respectively). Singh et al 12 found that Black individuals with SCD were more likely to be hospitalized and to develop pneumonia and pain, but no differences in mortality rate compared to matched Black individuals without SCD/SCT were observed, consistent with our findings.…”
supporting
confidence: 83%
“…However, SCD patients could have other severe outcomes not evaluated here (e.g., pain or pneumonia). 12 The mortality rate in our SCD patients (6%-8%) is comparable to those reported in the US 6 and UK registries 13 (7.3% and 8.4%, respectively). Singh et al 12 found that Black individuals with SCD were more likely to be hospitalized and to develop pneumonia and pain, but no differences in mortality rate compared to matched Black individuals without SCD/SCT were observed, consistent with our findings.…”
supporting
confidence: 83%
“…The higher morbidity and mortality from SARS-CoV-2 infection in African Americans are well documented. Overall, this study showed no difference in morbidity or mortality outcomes between individuals with and without SCT among patients admitted for SARS-CoV-2 infection, which mirrors the results from International Classification of Diseases, Tenth Revision code analysis by Singh et al 7 However, there were a few notable differences between the 2 groups. At the time of admission, individuals with SCT had significantly higher creatinine (median: 2.06 vs 1.15; P = .004) and lower EGFR ( P = .014) than those without SCT, consistent with the known higher rates of EGFR decline in patients with SCT.…”
Section: Resultssupporting
confidence: 86%
“…Other reports did not identify SCD as a risk factor for COVID-19 (32)(33)(34), or COVID-19 as a risk factor for SCD-mediated vaso-oclusive crisis (35). Nevertheless, patients with SCD have a predisposition to the development of pulmonary hypertension and chronic kidney disease (36).…”
Section: Discussionmentioning
confidence: 99%